2002
DOI: 10.1007/s11864-002-0039-7
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymph node metastases from occult squamous cell carcinoma

Abstract: Depending on patient and tumor characteristics, reported 5-year actuarial survival rates of patients with cervical nodal metastasis from an unknown primary carcinoma range from 18% to 63%. Prognostic factors for survival include N-stage, number of nodes, grading, extracapsular extension, and performance status. Retrospective studies suggest that neck relapse is more common than are distant metastases or emergence of mucosal primary tumors. The treatment options include neck dissection alone, radiation alone to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…Recent reviews have come to the conclusion that neck dissection and radiotherapy seem to have similar efficacy in early stages (N1), whereas more advanced cases (N2, N3) should be treated by combined approaches [1,5,6]. In our series of 46 patients with unknown primary, the mean survival time was 89 months.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Recent reviews have come to the conclusion that neck dissection and radiotherapy seem to have similar efficacy in early stages (N1), whereas more advanced cases (N2, N3) should be treated by combined approaches [1,5,6]. In our series of 46 patients with unknown primary, the mean survival time was 89 months.…”
Section: Discussionmentioning
confidence: 71%
“…The choice and the extent of diagnostic procedures are still under discussion [3,4]. There is no general consensus but routine diagnostic work-up typically includes physical examination, computed tomography (CT) or magnetic resonance imaging (MRI) of the neck, needle biopsy or excision of suspicious lymph nodes on the affected neck side, and directed biopsies of the upper aerodigestive tract during panendoscopy under anaesthesia [5,6]. Most would advocate at least ipsilateral tonsillectomy, as small tumours can be missed by a biopsy [1].…”
Section: Introductionmentioning
confidence: 99%
“…Erkal et al reported that 12 of 126 patients (10%) developed squamous cell carcinoma in the head and neck mucosa after initial treatment (9). In the review of Nieder et al, the median rate of emergence of the primary site after extensive radiotherapy was 9.5% (range 2-13%), whereas it was 8.0% (range 5-44%) after ipsilateral radiotherapy (8). As will be discussed later, IMRT with appropriate mucosal irradiation field settings is considered to lead to better treatment outcome by controlling the occult mucosal lesions.…”
Section: Discussionmentioning
confidence: 99%
“…However, little impact of CCRT on distant metastases has been observed [14]. ICT can reduce metastases incidence [15], and cisplatin-based ICT decreases the incidence of occult primary disease compared with RT [16,17]. There are other advantages of induction chemotherapy, particularly valued in the setting of unresectable disease.…”
Section: Discussionmentioning
confidence: 99%